2009
DOI: 10.14310/horm.2002.1245
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of amputation in diabetics with foot ulcer: Single center experience in a large Turkish cohort

Abstract: OBJECTIVE: Prediction of diabetic foot ulcer outcome may be helpful for clinicians in optimizing and individualizing management strategy. The aim of the present study was to examine the possibility of predicting the outcome of patients with diabetic foot ulcers by using easily assessed clinical and laboratory parameters at baseline. DESIGN: In this observational study, data were collected prospectively in 670 consecutive diabetic foot ulcer episodes in 510 patients examined between January 1999 and June 2008 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
98
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 27 publications
23
98
4
4
Order By: Relevance
“…Following the reading of the full text of the remaining 47 articles, 39 articles were excluded, including six reviews, 22 articles in which the data could not be extracted and 11 articles with duplicated populations. Finally, eight documents were included in this meta-analysis (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the reading of the full text of the remaining 47 articles, 39 articles were excluded, including six reviews, 22 articles in which the data could not be extracted and 11 articles with duplicated populations. Finally, eight documents were included in this meta-analysis (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Selby and Zhang (40) suggested that cigarette smoking was unrelated to amputation risk and a study by Stewart (41) indicated that cigarette smoking had no influence on diabetes mellitus-related amputation levels. By contrast, a number of studies have demonstrated that smoking is a significant covariate factor in diabetic foot amputation (25,30,42). The evidence supporting smoking as a risk factor is that heavy smokers are more prone to develop peripheral vascular disease that may result in a marked degree of arterial compromise, requiring amputation (41).…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Yesil S et al showed that the cut-off level of 90 mm/h for ESR had fair specificity for the prediction of major lower extremity amputations. 32 Another study of severe diabetic foot infections reported that the mean ESR in cases with osteomyelitis was only 56 mm/h. 31 In our study, we divided the patients into two groups: one group with ESR level < 50 mm/h (20.25%) and the other group with baseline ESR level of > 50 mm/h (79.75%).…”
Section: Resultsmentioning
confidence: 99%
“…Marston et al for the first time in 2006 reported that patients whose HbA1C was high during their study had more severe form of wound infection with higher incidence of amputation. 32,33 A target HbA1C of less than 7% is acceptable in all diabetic patients and the same is applicable for diabetic foot ulcer patients as well. This study indicates that the progression to the complication of diabetic foot ulcers was strongly correlated to the level of HbAlc as found in a similar study by Mohieldein AH et al 34 The data may suggest the beneficial effect of considering measurement of HbA1C as a routine test for diabetic patients and maintaining an optimum level of less than 7%.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Fakat ilerleyen durumlarda enfeksiyon tedavisinde en korkulan ve kaçınılma-ya çalıılan sonuç ekstremite amputasyonudur. Literatür incelendi¤inde amputasyon oranı %28 olarak bildirilirken, ülkemizde Yeil ve ark.nın [19] yaptıkları çalımada 1998-2008 yılları arasın-da bavuran 574 hastalık seride amputasyon oranı %37 olarak bildirilmitir. Bizim çalımamız küçük bir hasta grubunu kapsadı¤ı için bu açıdan de¤erlendirmemiz uygun olmayacaktır.…”
Section: Tartimaunclassified